Population dynamics of resident fish in a coastal lagoon under eutrophication-mediated habitat changes - GUERRERO-GÓMEZ, ADRIÁN; ZAMORA-LÓPEZ, ANTONIO; TORRALVA, MAR; ZAMORA-MARÍN, JOSÉ MANUEL; GUILLÉN-BELTRÁN, ANTONIO; OLIVA-PATERNA J., FRANCISCO (Mediterranean Marine Science, 2024)
Coastal lagoons, as transitional ecosystems, are crucial for providing ecosystem services and preserving fish communities, yet they face increasing pressures from anthropogenic activities. The Mar Menor coastal lagoon in the western Mediterranean exemplifies this challenge, as it suffers from severe eutrophication driven by agricultural and urban influences. In this study, we assess changes in the population dynamics of three resident fish species (Apricaphanius iberus, Pomatoschistus marmoratus, and Syngnathus abaster) in the context of human-induced impacts in the Mar Menor. Using long-term monitoring data (the reference period of 2002-2004 vs. the eutrophication period of 2015-2019), we analyze temporal variations in their population dynamics and their relationships with eutrophication-mediated structural changes in shallow waters. Our results suggest that these resident species, which are closely associated with shallow areas, show population dynamics that reflect habitat alterations, underscoring their potential as indicators of eutrophication impacts. This study enhances our understanding of the dynamics within transitional ecosystems and provides a basis for integrated management strategies aimed at promoting effective fish conservation.